2009
DOI: 10.1186/1477-7517-6-26
|View full text |Cite
|
Sign up to set email alerts
|

Can we prevent drug related deaths by training opioid users to recognise and manage overdoses?

Abstract: Background: Naloxone has been evidenced widely as a means of reducing mortality resulting from opiate overdose, yet its distribution to drug users remains limited. However, it is drug users who are most likely to be available to administer naloxone at the scene and who have been shown to be willing and motivated to deliver this intervention. The current study builds on a national training evaluation in England by assessing 6-month outcome data collected primarily in one of the participating centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 30 publications
7
71
0
Order By: Relevance
“…One study conducted in the UK found reductions in heroin use following naloxone training (Gaston, Best, Manning, & Day, 2009). This suggests such concerns may be unfounded, and addressing these unfounded perceptions may be important as part of pharmacist education.…”
mentioning
confidence: 99%
“…One study conducted in the UK found reductions in heroin use following naloxone training (Gaston, Best, Manning, & Day, 2009). This suggests such concerns may be unfounded, and addressing these unfounded perceptions may be important as part of pharmacist education.…”
mentioning
confidence: 99%
“…57 Ten strategies had a negligible or no impact on overdoses and deaths. 35,41,49,52,68,70,75,76,81,93 Five strategies had a small positive effect, 48,50,53,62,94 two had a moderate positive effect, 55,56 and four had a large positive effect, 60,63,69,82 which included (1) overdose prevention training and naloxone distribution, plus a change in the legal status of naloxone to permit its administration by any member of the public Most promising strategies by content and target audience Figure 5a and 5b show the impact of the strategies by content and target population. It suggests that the most promising strategies to improve appropriate use of opioids are (1) educational strategies aimed at health care professionals; (2) clinical strategies aimed at patients, opioid users, and health care professionals; and (3) collaborations.…”
Section: Impact On Overdose and Deathsmentioning
confidence: 99%
“…Among the 66 strategies described, 19 (29%) had some type of unintended consequence 41,42,[44][45][46]49,53,57,59,60,68,71,[73][74][75]79,82,84,90 and 4 reported no unintended consequence. 47,55,64,65 It was unclear in 43 studies whether there were any unintended consequences or not.…”
Section: Unintended Consequences Of Implemented Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These include concerns that many overdoses occur alone, addicts will be unable to recognise and respond to overdose, inappropriate use of naloxone may lead to complications or delay definitive care, some treated patients will be able to refuse care that is desperately needed, physicians will be reluctant to prescribe naloxone, and by making drug use safer overall use will increase. 25,35,36 Although the majority of these concerns have been discussed and settled in previous eras, they continue to resurface, possibly as a result of societal pressures and rooted belief systems.…”
Section: Limiting Opioid Deathsmentioning
confidence: 99%